IMPLEMENTATION OF ELECTION COMMISSION DECREE NUMBER 117 YEAR 2023 AMENDMENT TO GENERAL ELECTION COMMISSION DECREE NUMBER 68 YEAR 2023 CONCERNING TECHNICAL GUIDELINES FOR IMPLEMENTING THE SELECTION OF PROVINCIAL AND EGENCY/MUNICIPAL KPU MEMBERS IN CENTRAL - Kristiana, Tresia; Effrata, Effrata; Sentosa, Alfrid (FISIPOL Universitas PGRI Palangka Raya, 2023)
The General Election which will be held in 2024 simultaneously is the second general election in Indonesia. Simultaneous elections which are a combination of legislative elections (general elections for members of the DPR, DPD and DPRD) and general elections for the president and vice president. Basis for the implementation of the upcoming election Law No.7 of 2017 Concerning General Elections. One of the election management bodies is the General Election Commission. The problem in this research is how to implement the General Election Commission Decree No.117 of 2023 Amendment to KPKPU No.68 of 2023 concerning Technical Guidelines for Executing the Selection of Provincial Election Commission Members and Members of Regency/City General Election Commissions in Central Kalimantan Province. The results of the research in the implementation of the General Election Commission's decision are carried out according to the stages specified in the predetermined schedule. The Secretariat of the Central Kalimantan Provincial Election Commission is very helpful in the smooth implementation of the selection of prospective members of the Central Kalimantan Provincial Election Commission. There were no obstacles in implementation, the lack of facilities and infrastructure was carried out in collaboration with third parties, namely the Regional Personnel Agency for the Province of Central Kalimantan, and the Army Hospital.